Characterization of glucose oxidase from Penicillium notatum - Nawaz Bhatti, Haq (Array, 2009)
Summary: In the present study glucose oxidase (GOD) has been isolated from a culture filtrate of Penicillium notatum. The enzyme was purified by ammonium sulphate precipitation, diethylaminoethyl (DEAE) cellulose ion-exchange chromatography and Sephadex gel filtration. This protocol gave 16.47-fold purification and 25 % recovery of the enzyme. The optimum pH and temperature for the activity were 5.4 and 45 °C, respectively. The Km and vmax values for the enzyme were 10.5 mM and 456 U/mg, respectively. A detailed kinetic study of thermal inactivation was carried out. Both enthalpy of activation (ΔH*) and entropy of activation (ΔS*) decreased at higher temperatures. Moreover, free energy of denaturation (ΔG*) increased at higher temperature, making the enzyme thermally stable. A possible explanation for the thermal inactivation of GOD at higher temperatures is also discussed